Perbedaan Kemampuan Pemecahan Masalah Dan Komunikasi Matematis Siswa Yang Diajarkan Dengan Menggunakan Model Pembelajaran Talking Stick Dan Two Stay Two Stray Pada Materi SPLDV Di SMP Negeri 21 Medan - Selian, Nazri Maulana Khani; Sihombing, Fakhrur Rozi; Ritonga, Ade Irfan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to determine the differences in the learning models of the Talking Stick and Two Stay Two Stray types on problem-solving skills and mathematical communication skills. This research is quantitative research, with an experimental type of research. The population is all class VIII students of SMP Negeri 21 Medan, 2019-2020 School Year which amounts to 210 students. Data analysis was performed with Variance Analysis (ANAVA). The results of these findings show: 1) There are differences in the mathematical problem solving ability of students taught with the Talking Stick Learning model and the Two Stay Two Stray learning model, with an average score of > (52.57) (66.83). 2) There is a difference between the mathematical communication skills of students taught with the Talking Stick learning model and the Two Stay Two Stray learning model, with an average score of (64.53) > (71.13). 3) There is a difference between the problem-solving ability and mathematical communication ability of students taught with the Talking Stick learning model and students taught with the Two Stay Two Stray learning model, with Qhit (6,867) > Qtabel (2,814). Likewise on both capabilities with Qhit (5,353) > Qtabel (2,814). 4) There is a significant interaction between the learning model used on students' problem-solving ability and mathematical communication ability on the material of two-variable linear equations, with Fhitung (707.77) > FTabel (4.17). The conclusion of this study explains that students' problem-solving and mathematical communication skills are more appropriately taught with the Two Stay Two Stray model.